2009
DOI: 10.1111/j.1540-8159.2008.02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable Effects of Physical Training of Heart Rate Variability, Heart Rate Recovery, and Heart Rate Turbulence in Chronic Heart Failure

Abstract: Background: Heart rate variability (HRV), heart rate turbulence (HRT), and heart rate recovery (HRR), indices that reflect autonomic nervous system (ANS) activity, are outcome predictors in patients with chronic heart failure (CHF). It is not clear, however, whether they reflect the same components of ANS activity. No study has examined the effects of physical training (PT) training on HRV, HRT, and HRR in CHF. Study Objective: To examine the responses of HRV, HRT, and HRR to a PT program in patients presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 11 publications
(19 reference statements)
3
25
0
8
Order By: Relevance
“…10, 12, 14, 17, 20, 21, 23, 24 Results have been mixed, with most studies being small in size and based on either cross-sectional evaluations or short-term interventions. Studies evaluating PA and 24-hour HRV indices 11, 13, 15, 18, 19, 21, 22 were mostly performed in middle-aged populations and were also generally small and either cross-sectional evaluations or short-term interventions. Our findings build upon and extend these prior observations by longitudinally evaluating long-term, cumulatively updated PA and changes in PA with subsequent HRV, by evaluating nonlinear indices, and by analyzing different dimensions of PA including different aspects of walking.…”
Section: Discussionmentioning
confidence: 99%
“…10, 12, 14, 17, 20, 21, 23, 24 Results have been mixed, with most studies being small in size and based on either cross-sectional evaluations or short-term interventions. Studies evaluating PA and 24-hour HRV indices 11, 13, 15, 18, 19, 21, 22 were mostly performed in middle-aged populations and were also generally small and either cross-sectional evaluations or short-term interventions. Our findings build upon and extend these prior observations by longitudinally evaluating long-term, cumulatively updated PA and changes in PA with subsequent HRV, by evaluating nonlinear indices, and by analyzing different dimensions of PA including different aspects of walking.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,7 It has been reported that HRV indexes are modified by exercise training at different intensities, 8 been continuous endurance training of low and moderate intensities the most studied type of exercise related to HRV. 9,10 Although low to moderate exercise intensity (close to LT intensity) has been proposed systematically to modulate vagal activity, 9,10 to obtain complete adaptation in the cardiovascular system and vagal activity should be performed a combination of moderate and high intensity aerobic exercise. 11,12 Recent studies have shown than intermittent exercise may have an important role in achieving these goals, 13---15 however, these adaptations are both, primarily peripherally or acute effects and little is known about HRV, RPE, and lactate responses to intermittent exercise.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Regular physical exercise promotes a tonic decrease in sympathetic autonomic control and an increase in vagal control. 22,23 However, the effects of physical exercise and ACEis, alone or in combination, on heart-rate variability and the capacity for autonomic balance rearrangement (for example, during the tilt test) have not been investigated in hypertensive (HT) patients. We hypothesized that the association of hypertension treatment with ACEis and physical training provides greater effects on cardiac autonomic modulation and enhances the reduction of arterial pressure compared with either treatment in isolation.…”
Section: Introductionmentioning
confidence: 99%